2010
DOI: 10.1186/1750-9378-5-6
|View full text |Cite
|
Sign up to set email alerts
|

Multiple oncogenic viruses identified in Ocular surface squamous neoplasia in HIV-1 patients

Abstract: BackgroundOcular surface squamous neoplasia (OSSN) is a rare cancer that has increased in incidence with the HIV pandemic in Africa. The underlying cause of this cancer in HIV-infected patients from Botswana is not well defined.ResultsTissues were obtained from 28 OSSN and 8 pterygia patients. The tissues analyzed from OSSN patients were 83% positive for EBV, 75% were HPV positive, 70% were KSHV positive, 75% were HSV-1/2 positive, and 61% were CMV positive by PCR. Tissues from pterygium patients were 88% posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
3
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 47 publications
5
52
3
1
Order By: Relevance
“…The direct association and contribution of some of the parasites and the vector moieties to the overall pathology of the cancer is not known. Interestingly, we observed a greater number of herpes type viruses that have been associated with oncogenesis (McDonnell, 1986;Simbiri et al, 2010;Hoshikawa, Satoh, Murakami, et al 2002), and bacteria, parasites, and fungi whose co-infection leads to enhanced immunosuppression of the HIV infected host (Lloyd-Smith, Poss, & Grenfell, 2008;Barnabas, Webb, Weiss, & Wasserheit, 2011). Fungal S. pombe and the common free living soil nematode C.elegans were also detected.…”
Section: Glossina Palpalismentioning
confidence: 87%
See 3 more Smart Citations
“…The direct association and contribution of some of the parasites and the vector moieties to the overall pathology of the cancer is not known. Interestingly, we observed a greater number of herpes type viruses that have been associated with oncogenesis (McDonnell, 1986;Simbiri et al, 2010;Hoshikawa, Satoh, Murakami, et al 2002), and bacteria, parasites, and fungi whose co-infection leads to enhanced immunosuppression of the HIV infected host (Lloyd-Smith, Poss, & Grenfell, 2008;Barnabas, Webb, Weiss, & Wasserheit, 2011). Fungal S. pombe and the common free living soil nematode C.elegans were also detected.…”
Section: Glossina Palpalismentioning
confidence: 87%
“…Our study of OSSN tissues from Botswana HIV-1 infected patients has led to significant findings, namely the association of multiple oncogenic viruses with this cancer (Simbiri et al, 2010). In the current study through cloning and pyrosequencing, our results showed sequences of additional viruses, bacteria, fungi, and parasites in the sera of the patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Иммуногистохими-ческие исследования удаленного материала у ВИЧ инфицированных пациентов по поводу СНГП выявили мультифакториальную приро-ду новообразования. Так, в гистологических срезах определялись такие онкогенные вирусы как вирус папилломы человека, Эпштейна-Барр и саркомы Капоши [24].…”
Section: этиология и патогенезunclassified